Midwifery Care of Newborn Baby Mrs "N" with Low Birth Weight in BLUD Tenriawaru Public Hospital in Class B, Bone Regency (Jurnal Suara Kesehatan, 2021)
Low birth weight (LBW) is still a problem around the world, because it causes morbidity and mortality in the neonatal period. The prevalence of LBW is still quite high, especially in countries with low socio-economic conditions. Statistically, 90% of the incidence of LBW is found in developing countries and the mortality rate is 35 times higher than in infants with birth weight> 2500 g. This observational study also conducted interviews with the client's family and midwives regarding the client's problems. The author obtains data by seeing and monitoring the patient directly. The method used in the author is a case study report. Then a physical examination. The author performs a physical examination of the patient through systematic examination, palpation, auscultation and percussion from head to toe and laboratory examinations as a supporting examination. The results of the study revealed that the data on Mrs. “N” babies as a whole were a sign of LBW as described in the theory of the portion of signs and symptoms experienced by clients, namely LBW 37-42 weeks of gestation with a body weight of <2500 grams. The real problem is LBW which upholds basic diagnostic determinations according to the literature. It seems clear that there are parallels between the existing theory and the case study of Mrs "N "'s baby. Low birth weight is very susceptible to hypothermia and impaired nutrition. In conclusion, all the measures to be performed on Mrs. "N" baby are well planned to treat low birth weight babies and their possible complications. In the implementation of Midwifery Care for Mrs “N” babies, it is planned that her actions will be carried out in full.